2019
DOI: 10.1038/s41598-019-46169-w
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation regime change in Western North America: The role of Atmospheric Rivers

Abstract: Daily precipitation in California has been projected to become less frequent even as precipitation extremes intensify, leading to uncertainty in the overall response to climate warming. Precipitation extremes are historically associated with Atmospheric Rivers (ARs). Sixteen global climate models are evaluated for realism in modeled historical AR behavior and contribution of the resulting daily precipitation to annual total precipitation over Western North America. The five most realistic models display consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
176
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 63 publications
21
176
1
4
Order By: Relevance
“…Nevertheless, AR contribution to total precipitation, although variable from year to year, historically amounts to ~ 40% of the climatological annual total climatological precipitation along the West Coast of North America and in excess of 50% in coastal Northern California-a bullseye of AR landfalling activity ). This historical contribution of ARs to Western water resources is clearly projected to increase with future warming (Gershunov et al 2019). Figure 14a, b shows ERA-Interim geopotential height (Z) anomalies at 500 hPa for winter AR days occurring in two coastal latitude bands (Gao et al 2015).…”
Section: Atmospheric Riversmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, AR contribution to total precipitation, although variable from year to year, historically amounts to ~ 40% of the climatological annual total climatological precipitation along the West Coast of North America and in excess of 50% in coastal Northern California-a bullseye of AR landfalling activity ). This historical contribution of ARs to Western water resources is clearly projected to increase with future warming (Gershunov et al 2019). Figure 14a, b shows ERA-Interim geopotential height (Z) anomalies at 500 hPa for winter AR days occurring in two coastal latitude bands (Gao et al 2015).…”
Section: Atmospheric Riversmentioning
confidence: 99%
“…A progressively larger proportion of California's total annual precipitation is projected to be generated in heavy and extreme events (Polade et al 2017), however, further increasing the natural volatility of the regional hydroclimate. This projected intensification of extremes has recently been attributed to mainly thermodynamic bolstering of ARs in a warming climate (Gershunov et al 2019). This is one regional example, for a region with a diverse and growing population and over-allocated water resources that hinge on mountain snowpack, which is additionally affected by the warming trend.…”
Section: Role Of Lsmps and Large-scale Influences In Trendsmentioning
confidence: 99%
“…The presence of ARs plays an important role for regional precipitation, which could include rain or snow (Dettinger et al, ; Guan et al, ); they can also cause large flooding events (Lavers et al, ; Leung & Qian, ; Neiman et al, ; Ralph et al, , ; Ralph & Dettinger, ) and extreme winds (Waliser & Guan, ), but they can also mitigate droughts (Dettinger, ). This large impact has motivated several studies on ARs related to climate change, with most studies focusing on Europe (Gao et al, ; Lavers et al, ; Ramos et al, ; Shields & Kiehl, ) and western North America (Dettinger, 2011; Pierce et al, ; Payne & Magnusdottir, ; Warner et al, ; Gao et al, ; Radić et al, ; Hagos et al, ; Shields & Kiehl, , ; Gershunov et al, ), with the exception of Espinoza et al (), which provided a global view of AR frequency and strength in future climates.…”
Section: Introductionmentioning
confidence: 99%
“…, Gershunov et al. ), and many river systems have shown increasing flow variation in response (Milly et al. , Rahmstorf and Coumou , Coumou and Rahmstorf , Ward et al.…”
Section: Introductionmentioning
confidence: 99%
“…Life history analysis also can inform an understanding of how land use and climate change may affect freshwater fish populations. The rate of extreme precipitation events has increased in many regions globally over recent decades (Easterling et al 2000, Gershunov et al 2019, and many river systems have shown increasing flow variation in response (Milly et al 2008, Rahmstorf and Coumou 2011, Coumou and Rahmstorf 2012, Ward et al 2015. Urbanization and forestry practices also can increase flashiness of downstream flows (O'Driscoll et al 2010).…”
Section: Introductionmentioning
confidence: 99%